Effect of calcium carbonate and sucrose addition on the properties of roselle extract using response surface methodology - Wan Zawiah Wan Abdullah,; Md Zaidi Yahaya,; Mohamad Yusof Maskat, (Universiti Kebangsaan Malaysia, 2012)
This study was conducted to determine the effect of calcium carbonate (CaCO3) and sucrose addition on roselle extract using Response Surface Methodology. A total of 21 treatments were used based on a Central Composite Rotatable Design (CCRD). Determination of pH and Brix were carried out. For pH, the model used was 4.03+0.39x1-8.20x2-0.05x12-4.16x22-0.02x1x2 where x1 is calcium carbonate and x2 is sucrose. The positive coefficient for calcium carbonate showed addition of calcium increased pH of the roselle extract. Model for Brix is 8.91 + 0.23x1 + 2.20x2. The positive coefficient for calcium carbonate and sucrose showed the addition of calcium carbonate and sucrose increased the degree of Brix of the roselle extract. Sensory evaluation using trained panelists (n=8) showed addition of sucrose increased overall acceptance for roselle extract. Addition of calcium carbonate reduced the overall acceptance due to the lowering of the sour taste.